Implemetasi Algoritma Binary Search Dalam Pengembangan Aplikasi Mobile Android Untuk Kamus Sinonim Dan Antonim - Desi Novita Sari; Maryaningsih Maryaningsih; Abdussalam Al Akbar (UNIVED Press, 2026)
This research aims to implement the Binary Search algorithm in the development of an Android mobile application for a dictionary of synonyms and antonyms to improve the efficiency of the data search process. The application development method used in this research is the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. The Binary Search algorithm is applied to the search process for words that have been sorted alphabetically, thus speeding up search times compared to linear search methods. This application was developed using the Java/Kotlin programming language and a local database to store the collection of words along with their synonyms and antonyms. Test results show that implementing the Binary Search algorithm significantly increases word search speed and provides accurate results.